2014
DOI: 10.1177/0269758014521741
|View full text |Cite
|
Sign up to set email alerts
|

Teens’ self-efficacy to deal with dating violence as victim, perpetrator or bystander

Abstract: Multiple studies have demonstrated that adolescent dating violence is highly prevalent and associated with internalizing and externalizing problems. A number of prevention initiatives are being implemented in North-American high schools. Such initiatives do not only aim to raise awareness among potential victims and offenders but also among peer bystanders. Since teenagers mainly reach out to their peers when experiencing adversity, it is important to address adolescents' efficiency to deal with witnessing dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 71 publications
1
23
1
3
Order By: Relevance
“…Interestingly, many of the barriers and facilitators of bystander action in situations of dating and sexual aggression we documented are similar to barriers and facilitators of bystander action documented in the bullying literature (Ferrans et al 2012;Pozzoli and Gini 2010a, b;Pozzoli et al 2012). Girls were more likely than boys to intervene in situations of dating and sexual aggression, which is consistent with previous research (Jaffe et al 1992;Van Camp et al 2014). Extending previous research, we found that boys and girls also used different methods of intervention (e.g., girls were more likely to talk to the victim whereas boys were more likely to use physical aggression with the perpetrator), suggesting that gender-specific educational messages may be needed in bystander prevention programming with youth.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Interestingly, many of the barriers and facilitators of bystander action in situations of dating and sexual aggression we documented are similar to barriers and facilitators of bystander action documented in the bullying literature (Ferrans et al 2012;Pozzoli and Gini 2010a, b;Pozzoli et al 2012). Girls were more likely than boys to intervene in situations of dating and sexual aggression, which is consistent with previous research (Jaffe et al 1992;Van Camp et al 2014). Extending previous research, we found that boys and girls also used different methods of intervention (e.g., girls were more likely to talk to the victim whereas boys were more likely to use physical aggression with the perpetrator), suggesting that gender-specific educational messages may be needed in bystander prevention programming with youth.…”
Section: Discussionsupporting
confidence: 89%
“…Further, although Van Camp et al (2014) found that a history of dating aggression victimization was unrelated to likelihood of intervening in situations of dating aggression among Canadian high school youth, McCauley et al (2013) found that as likelihood to intervene in dating aggression situations increased among high school athletes, the likelihood of perpetrating dating aggression decreased.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Some studies found differences in bystander intervention based on youth demographic characteristics. Three studies showed that female youth are more likely to intervene and more optimistic about their intervention abilities (Edwards et al, 2015; Fry et al, 2014; Hébert, Van Camp, Lavoie, Blais, & Guerrier 2014; Van Camp et al, 2014). Moreover, Fry and colleagues (2013) and Sargent and colleagues (2017) found that Hispanic adolescents were more likely to use bystander intervention than non-Hispanic adolescents.…”
Section: Resultsmentioning
confidence: 99%